Pemanfaatan Digital Marketing dan Pengelolaan Keuangan Pada Toko Bahan Kue - Ni Luh Ratniasih; Dwi Haryadi Nugraha (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
Competition in the cake and bread business is quite tight, this is marked by the emergence of the same business, and the increasing variety of breads and cakes offered. The development of culinary business is also seen from the number of shops opened baking cake ingredients. Partners in this service activity are a cake ingredients shop and sell pastries located in the Denpasar city market area. The name of the partner shop is